2003
DOI: 10.1177/0001699303046002005
|View full text |Cite
|
Sign up to set email alerts
|

The Reality of Experts and the Imagined Lay Person

Abstract: Once scholars start to think about knowledge societies, at some point in their analyses they have to leave the realms of purely academic interactions among scientists in their sanitized production of knowledge. Conceptions of lay persons then come to the fore. Unfortunately, this realm of interaction traditionally has been far less subject to scholarly scrutiny. The focus of most studies is usually on knowledge, or to be more precise, scientific knowledge, with an odd confidence that this knowledge will faithf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
99
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 13 publications
1
99
0
1
Order By: Relevance
“…We have focused here on how developers construct opponents. This is significant because the characteristics of such ''imagined publics'' (Maranta et al 2003) inform their modes of public engagement and may also inform and influence public responses themselves. Developers' constructions of local publics are potentially significant in shaping how the dynamics of local responses evolve and how different actors react and strategically behave in relation to each other over both the short and longer term.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have focused here on how developers construct opponents. This is significant because the characteristics of such ''imagined publics'' (Maranta et al 2003) inform their modes of public engagement and may also inform and influence public responses themselves. Developers' constructions of local publics are potentially significant in shaping how the dynamics of local responses evolve and how different actors react and strategically behave in relation to each other over both the short and longer term.…”
Section: Resultsmentioning
confidence: 99%
“…Research in various spheres has illustrated that the ways in which experts construct or imagine publics has implications for their patterns of engagement with them (e.g., Maranta et al 2003, Stilgoe 2007Burningham et al 2007). Barnett et al (2012) indicate that expectations of antagonistic public responses lead RET developers to prefer top-down processes of information provision, with the result that local publics often feel that their concerns have not been taken seriously, thus fueling their discontent.…”
Section: Constructing Publics and Public Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…The public understanding of science (PUS) literature has considered imagined or constructed publics to a fair extent with regards to for instance how experts attempt to make scientific knowledge socially robust through the help of Imagined Lay Persons (ILPs) (Maranta et al, 2003). Applying this concept, Walker et al (2010) found that the public opinion on the technological development of renewables raised concerns in experts, making them incorporate in their projects a semi-real but very significant subjectivity based on a mix of direct interactions with and anticipations about the public.…”
Section: Technology Expectations Imagined Publicsmentioning
confidence: 99%
“…It prevents the development of insights about how people reach the wrong conclusion, why they draw conclusions so quickly, and what the 5 The conclusion that non-experts reach 'inappropriate' or 'wrong conclusions' has often been used by experts to disqualify public opinion, while claiming that they themselves are 'right' (Hansen, Holm, Frewer, Robinson, & Sandøe, 2003). Thus, claims that non-experts are wrong can be highly political (Maranta, Guggenheim, Gisler, & Pohl, 2003) and met with suspicion. However, this of course does not mean that non-experts cannot be wrong.…”
Section: Instead People Form What Is Known As Lay Expertisementioning
confidence: 99%